HUBUNGAN PARITAS TERHADAP KEJADIAN PERSALINAN LAMA DI RSUD PRINGSEWU TAHUN 2014 - Hasyim, Dzul Istiqomah; Budianto, Apri; Dhona, Rhoma (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Based on the WHO (World Health Organization) in 2010, confirmed every year around the world 358 000 women die during pregnancy or child birthin which 355,000 mothers (99%) came from developing countries. According to the department of healthin 2010, the direct cause of maternal deaths in Indonesia related to pregnancy and child birth mainly is bleeding 28%. For another, namely eclamption24%, infection 11%, prolonged labor5%, and abortion 5%. Prolongedlaboris caused by several factors, one of which is a factor of parity, especially in primiparous women. From the research that has been done can be concluded that there is a relationship of parity with the incidence of prolonged labor. The aim in this study was to determine the relationship between maternal parity with the prolonged Labor incidentin RSUD Pringsewu 2014. The study design use discroos sectional, with a sample of 321 respondents, the sampling technique used total sampling with chi-square test. Results of the study there was a relationship between maternal paritywith the incidence of prolonged laborin RSUD Pringsewu 2014. With 0,002 value Ï (Ï <Î± =0.05). Maternal primigravidas more at risk of prolonged labor. By looking at the results of this research are expected as a means to add insight and information about parity as one of the factors the occurrence of prolonged labor. Key Word: Parity, Prolonged labor